OsGRF4AA compromises heat tolerance of developing pollen grains in rice - Mo, Yujian; Li, Guangyan; Liu, Li; Zhang, Yingjie; Li, Junyi; Yang, Meizhen; Chen, Shanlan; Lin, Qiaoling; Fu, Guanfu; Zheng, Dianfeng; Ling, Yu (Frontiers in Plant Science, 2023)
Extreme high temperature at the meiosis stage causes a severe decrease in spikelet fertility and grain yield in rice. The rice variety grain size on chromosome 2 (GS2) contains sequence variations of OsGRF4 (Oryza sativa growth-regulating factor 4; OsGRF4AA), escaping the microRNA miR396-mediated degradation of this gene at the mRNA level. Accumulation of OsGRF4 enhances nitrogen usage and metabolism, and increases grain size and grain yield. In this study, we found that pollen viability and seed-setting rate under heat stress (HS) decreased more seriously in GS2 than in its comparator, Zhonghua 11 (ZH11). Transcriptomic analysis revealed that, following HS, genes related to carbohydrate metabolic processes were expressed and regulated differentially in the anthers of GS2 and ZH11. Moreover, the expression of genes involved in chloroplast development and photosynthesis, lipid metabolism, and key transcription factors, including eight male sterile genes, were inhibited by HS to a greater extent in GS2 than in ZH11. Interestingly, pre-mRNAs of OsGRF4, and a group of essential genes involved in development and fertilization, were differentially spliced in the anthers of GS2 and ZH11. Taken together, our results suggest that variation in OsGRF4 affects proper transcriptional and splicing regulation of genes under HS, and that this can be mediated by, and also feed back to, carbohydrate and nitrogen metabolism, resulting in a reduction in the heat tolerance of rice anthers.